High-compactness composite current collector preparation device and application thereof

By using a high-density composite fluid collection preparation device in the composite fluid collection preparation process, spraying the conductive adhesive layer and scraping the coating flat, combining argon to fill the gap, the problems of coating inclination and copper layer diffusion and stickiness are solved, and the problem of coating inclination and copper layer diffusion and stickiness is achieved High density and strength composite liquid collector preparation improves battery performance.

CN119387115APending Publication Date: 2025-02-07JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411377449.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing composite fluid collection preparation process, the inclination angle of the coating after spraying causes surface collapse and deformed folds, and the diffusion and sticking between the copper layers lead to the coating to fall off, affecting the energy density, cycle life and safety of the battery.

Method used

Using a high-density composite fluid packing preparation device, including a mounting unit and a coating unit, spraying conductive adhesive layer on the surface of the base film by spraying the coating part, and scraping the flat coating with serrated racks in the scraping assembly to reduce air foam and Inhomogeneity. At the same time, argon gas is filled with argon gas tank, and the conductive glue gap is filled during winding to prevent the film surface from collapse.

Benefits of technology

It effectively reduces the risk of bubbles and wrinkles on the surface of the coating, improves the density and tensile strength of the composite fluid collection, prevents the copper layer from falling off, and improves the energy density, cycle life and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387115A_ABST
    Figure CN119387115A_ABST
Patent Text Reader

Abstract

The invention discloses a high-compactness composite current collector preparation device and application thereof, and relates to the technical field of current collector preparation, and the high-compactness composite current collector preparation device comprises an installation unit which comprises an installation bottom plate, an installation shell arranged on the installation bottom plate, an unwinding device arranged on the installation shell and a winding device arranged on the installation shell; and the coating unit comprises a spraying part arranged on the mounting shell, an extrusion roller arranged on the spraying part and an argon tank arranged below the spraying part. Through the arrangement of the spraying part, a base film passes through a scraper and a sawtooth-shaped rack after being sprayed with a coating, air foam in the coating can be broken, air entrainment is reduced, the risk that bubbles and wrinkles are generated on the surface of the coating is reduced, and before the coating reaches an inclined or folded area, the sawtooth-shaped rack can firstly smooth the surface of the coating, so that the coating is prevented from falling off. Deformation of the coating during inclination is reduced, and high compactness of a product can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collector preparation, and in particular to a high-density composite current collector preparation device and application thereof. Background Art

[0002] With the rapid development of new energy and electronic technology, the cycle life, safety performance, energy density, etc. of batteries have become top priorities. As a very important part of the battery, the current collector is used to collect the current generated by the active materials of the battery in order to form a larger current output. Its performance will directly affect the cycle life, energy density, safety, etc. of the battery.

[0003] At present, the positive and negative electrodes in lithium batteries and sodium batteries mostly use copper foil and aluminum foil as current collectors. This type of current collector has high cost and quality, which is not conducive to controlling battery costs and improving energy density. In this regard, composite foil has obvious advantages over traditional foil. Composite foil current collectors are usually a "sandwich" structure, with a polymer layer on the inner layer and metal conductive layers on both sides. In the current industrial mass-produced composite current collector, the composite aluminum foil usually uses 1-6μm polyethylene terephthalate or polypropylene as the substrate, and then magnetron sputtering is used to plate a 30-60nm copper layer on both sides of the substrate, and then a 1μm copper layer is obtained by water plating. Although the composite foil has the advantages of low cost and light weight, in the production process, it often has an inclination angle when entering the next processing link after spray coating, which causes the coating surface to collapse and cause deformation and wrinkles. At the same time, under the influence of winding speed, cooling, vacuum, winding tension, conductive glue coating and argon filling, the copper atoms between the copper layers will diffuse and stick, causing the coating to fall off, making the composite material dense and transparent, and the square resistance decreases, thereby affecting the energy density, cycle life and safety of the battery. At present, there is no ideal solution for making high-density composite current collectors.

[0004] Therefore, it is necessary to propose a high-density composite current collector preparation device and its application. Summary of the invention

[0005] In view of the above-mentioned problems existing in the existing high-density composite current collector preparation device, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to provide a high-density composite current collector preparation device, which aims to solve the technical problem that during the magnetron sputtering production process, there is often an inclination angle when entering the next processing link after spraying the coating, causing the coating surface to collapse and cause deformation and wrinkles.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0008] The mounting unit comprises a mounting base plate, a mounting shell arranged on the mounting base plate, an unwinding device arranged on the mounting shell, and a rewinding device arranged on the mounting shell;

[0009] The coating unit comprises a spray coating part arranged on the mounting shell, an extrusion roller arranged on the spray coating part, and an argon gas tank arranged under the spray coating part.

[0010] As a preferred solution of the high-density composite current collector preparation device of the present invention, the spraying part includes a spraying component arranged on the mounting shell, and a scraping component arranged on the mounting shell.

[0011] As a preferred solution of the high-density composite current collector preparation device of the present invention, the spraying assembly includes a spray chamber arranged on the mounting shell, and a nozzle arranged on the spray chamber.

[0012] As a preferred solution of the high-density composite current collector preparation device of the present invention, the scraping assembly includes a scraper disposed on the nozzle, and a serrated toothed rack disposed on the scraper;

[0013] The tip angle of the sawtooth rack is 60°.

[0014] The beneficial effects of the present invention are as follows: by setting up the spraying part, after the coating is sprayed on the base film of the magnetron sputtering copper layer, it passes through the scraper and the serrated rack, which helps to break the air bubbles in the coating and reduce air entrainment, thereby reducing the risk of bubbles and wrinkles on the coating surface. Before the coating reaches the inclined or folded area, the serrated rack can first smooth the coating surface, reduce the deformation of the coating when tilted, and help to achieve high density of the product.

[0015] Another object of the present invention is to provide an application of a high-density composite current collector preparation device, the purpose of which is to solve the technical problem that the copper atoms on the base film diffuse and stick together between the copper layers on the base film during magnetron sputtering, causing the coating to fall off, making the composite material dense and light-transmissive, and reducing the square resistance, thereby affecting the energy density, cycle life and safety of the battery.

[0016] In order to solve the above technical problems, the present invention provides the following technical solution: comprising: winding the base film on the unwinding (103), -3 Pa, start the device, keep the vacuum of the reel (104) at 0.5-1 Pa, plate a copper layer on the base film by magnetron sputtering, and then spray a conductive adhesive layer on the surface of the base film through a spraying part (201) by dot coating;

[0017] The base film after spraying the conductive adhesive layer is heated and cooled respectively and then moved to a roll (104) under an argon atmosphere to obtain a high-density composite current collector;

[0018] Wherein, the base film comprises 4.5 μm PP, PET, PE or PI.

[0019] As a preferred application scheme of the high-density composite current collector preparation device of the present invention, wherein: the thickness of the conductive adhesive layer is 5 to 10 nm.

[0020] As a preferred application scheme of the high-density composite current collector preparation device of the present invention, the base film is heated at a temperature of 40 to 50°C.

[0021] As a preferred application scheme of the high-density composite current collector preparation device of the present invention, the base film is cooled to a temperature of -20 to -10°C.

[0022] As a preferred application scheme of the high-density composite current collector preparation device of the present invention, wherein: the linear speed of the winding and unwinding is 3 to 10 m / min.

[0023] The beneficial effects of the present invention are as follows: by spraying a conductive adhesive layer on the outside of the copper layer, due to the high viscosity of the conductive adhesive, the tensile strength of the conductive adhesive is higher than that of the copper film, and the conductive adhesive can block the adhesion between the copper layers when the base film of the magnetron sputtered copper layer is rolled up, so that the copper layer on the base film will not fall off due to the adhesion of the copper layers to each other, thereby improving the density and tensile strength of the composite current collector after water plating, and at the same time, adding an argon tank to fill the winding chamber with argon. During winding, the argon fills the gaps in the conductive adhesive to play a supporting role, preventing the collapse of the film surface and causing defects such as deformation and wrinkles. The process control during the magnetron sputtering process, the isolation of the conductive adhesive during the winding process, and the control of the vacuum degree can effectively reduce the problems of copper atom diffusion on the winding film surface after magnetron sputtering, and improve the key performance of the composite current collector such as the density and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0025] Figure 1 It is a schematic diagram of the overall structure of the device for preparing a high-density composite current collector of the present invention.

[0026] Figure 2 It is a schematic diagram of the cross-sectional structure of the device for preparing the high-density composite current collector of the present invention.

[0027] Figure 3 It is a schematic diagram of the cross-sectional structure of the device for preparing the high-density composite current collector of the present invention.

[0028] Figure 4 It is a schematic diagram of the overall structure of the spraying part of the high-density composite current collector preparation device of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] Secondly, the present invention is described in detail with reference to the schematic diagram. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0033] The conductive adhesive used in the present invention is Parker model: Type 568 Nickel Filled Epoxy Coating.

[0034] The compactness (light transmittance) test method of the present invention is as follows: the composite current collector sample prepared as above is placed closely on a common plane backlight (brightness of 1200 mL) in a dark room, the length and width of the sample are larger than the backlight plate by 30 cm*30 cm, and the photo taken at a vertical angle shows that the light-transmitting area is a non-dense area, and the light-impermeable area is a dense area of ​​the copper layer;

[0035] Density = area of ​​non-dense area of ​​copper layer / area of ​​backlight panel ≤ 1% is qualified.

[0036] Tensile strength test method: bake the above composite current collector at 150℃ for 3min, cut into 15mm wide copper film strips in MD or TD direction, the edge of the strip to be tested should not have gaps, burrs, and soft or hard defects on the film surface. Set the running speed of the tensile testing machine to 50mm / min and the stretching distance to 50mm, place the copper film strip of the sample to be tested in the upper and lower chucks, so that the copper film strip is clamped and tensioned on the tensile testing machine, and perform tensile testing: the tensile strength in MD direction ≥200Mpa or the tensile strength in TD direction ≥180Mpa is qualified.

[0037] The water plating solution used in the present invention specifically includes the following raw materials: 0.05 g / L ethylenediamine, 100 g / L copper sulfate, 120 g / L sulfuric acid, the rest is pure water, and 60 ppm chloride ions;

[0038] The water plating process is: bath temperature 24°C, plating time 4min, current 7755A.

[0039] Example 1

[0040] Reference Figure 1-2 , which is the first embodiment of the present invention, provides a high-density composite current collector preparation device, the device comprising:

[0041] The mounting unit 100 includes a mounting base plate 101, a mounting housing 102 disposed on the mounting base plate 101, an unwinding device 103 disposed on the mounting housing 102, and a rewinding device 104 disposed on the mounting housing 102. The base film is wound on the unwinding device 103, and the device is opened to move it toward the rewinding device 104.

[0042] The coating unit 200 includes a spraying part 201 arranged on the installation shell 102, an extrusion roller 202 arranged on the spraying part 201, and an argon gas tank 203 arranged under the spraying part 201. The conductive adhesive layer is sprayed onto the surface of the base film through the spraying part 201, and the conductive adhesive layer is reinforced under the action of the extrusion roller 202.

[0043] Among them, the spraying part 201 includes a spraying component 201a arranged on the mounting shell 102, and a scraping component 201b arranged on the mounting shell 102. After the conductive adhesive layer is formed on the surface of the base film by the spraying component 201a, the bubbles or unevenness on the surface of the conductive adhesive layer are scraped and flattened when the base film passes through the scraping component 201b, thereby improving the density of the conductive adhesive layer.

[0044] During use, the base film is wound on the unwinding 103, and the device is opened to move it toward the winding 104. The vacuum degree of the winding 104 is adjusted by the argon tank 203. After the copper film is sputtered on the surface of the base film, it moves to the spraying part 201. The conductive adhesive layer is sprayed on the surface of the base film by the spraying part 201, and the conductive adhesive layer is reinforced under the action of the squeezing roller 202. After the conductive adhesive layer is sprayed on its surface by the spraying component 201a, the surface is flattened by the scraping component 201b, so as to avoid the presence of bubbles or wrinkles on the surface of the conductive adhesive layer that affect the density.

[0045] Example 2

[0046] Reference Figure 1-4 , which is the second embodiment of the present invention. This embodiment is different from the first embodiment in that: the spraying component 201a includes a spraying chamber 201a-1 arranged on the mounting shell 102, and a nozzle 201a-2 arranged on the spraying chamber 201a-1. When the base film moves to the spraying component 201a, the conductive glue in the spraying chamber 201a-1 is sprayed to the surface of the base film through the nozzle 201a-2 to form a conductive glue layer.

[0047] Compared with Example 1, further, the scraping assembly 201b includes a scraper 201b-1 arranged on the nozzle 201a-2, and a serrated rack 201b-2 arranged on the scraper 201b-1; when the conductive adhesive layer on the surface of the base film moves to the scraping assembly 201b, it is scraped and leveled by the scraper 201b-1, and the thickness of the coating is set by the serrated rack 201b-2, and the transfer amount of the coating is controlled by adjusting the gap between the scraper 201b-1 and the squeezing roller 202, and at the same time, the air bubbles in the conductive adhesive layer are broken, and air entrainment is reduced, thereby reducing the risk of bubbles and wrinkles on the coating surface;

[0048] The tip angle of the serrated rack 201b-2 is 60°. Each "tooth" of the serrated scraper 201b-1 can evenly distribute the coating and reduce the stripes and unevenness of the coating. Before the coating reaches the inclined or folded area, the serrated scraper 201b-1 can first smooth the coating surface to reduce the deformation of the coating when tilted, and effectively prevent the accumulation of coating on the coating head or the edge of the foil to avoid wrinkles.

[0049] The remaining structures are the same as those of Example 1.

[0050] Example 3

[0051] Reference Figure 1-4 , which is the third embodiment of the present invention, is based on embodiments 1 to 2, and provides an application of a high-density composite current collector preparation device, comprising:

[0052] The 4.5 μm PP base film was wound on the unwinding 103 and -3 Pa, start the device, start the argon tank 203, keep the vacuum of the winding 104 at 0.5Pa, use high vacuum winding magnetron sputtering equipment, use Cu as the target material, and perform plasma treatment under argon gas with a plasma voltage of 1000V and 30sccm. Set the cooling temperature of the main roller of the winding coating to -20°C, the sputtering target distance to 10cm, the target power to 10kw, and the argon gas flow rate to 50sccm for magnetron sputtering coating, and plate a 50nm copper layer on the base film. After that, the base film is sprayed with a 10nm conductive adhesive layer on its surface by a dot coating method through the spraying part 201, wherein the line speed of the winding and unwinding is 10m / min;

[0053] The base film after spraying the conductive adhesive layer is heated to 50° C. and cooled to -20° C. under 400GS magnetic field conditions and then moved to the reel 104 under argon atmosphere to obtain a semi-finished composite current collector. The surface of the semi-finished composite current collector is water-plated to obtain a 1 μm copper layer on both sides to obtain a high-density composite current collector.

[0054] The performance of the high-density composite current collector prepared in Example 3 was tested, and the results are shown in Table 1.

[0055] Table 1

[0056]

[0057] It can be seen from Table 1 that the composite current collector prepared by the present invention has a specific high density while taking into account its mechanical strength such as tensile properties. Its excellent bonding force can prevent the copper layer from sticking to each other during winding, so that the copper layer will not fall off due to the mutual adhesion of the copper layers. Therefore, the density and tensile strength of the composite current collector can be improved after water plating. An argon tank is added at the winding place to fill the winding chamber with argon. When winding, the argon fills the gaps in the conductive adhesive to play a supporting role, thereby preventing the collapse of the membrane surface and causing defects such as deformation and wrinkles.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 3 is that the thickness of the conductive adhesive layer is adjusted to 5 nm, and the other conditions are consistent with those of embodiment 3, so as to obtain the high-density composite current collector of embodiment 4.

[0060] Example 5

[0061] The difference between this embodiment and embodiment 3 is that the heating temperature is adjusted to 40° C., and the other conditions are consistent with those of embodiment 3, thereby obtaining the high-density composite current collector of embodiment 5.

[0062] Example 6

[0063] The difference between this embodiment and embodiment 3 is that the cooling temperature is adjusted to -10°C, and the other conditions are consistent with those of embodiment 3, thereby obtaining the high-density composite current collector of embodiment 6.

[0064] Example 7

[0065] The difference between this embodiment and embodiment 3 is that the linear speed of the winding and unwinding is adjusted to 5 m / min, and the other conditions are consistent with those of embodiment 3, so as to obtain the high-density composite current collector of embodiment 7.

[0066] Comparative Example 1

[0067] Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that no conductive adhesive layer is coated, and the other conditions are consistent with Example 3, so as to obtain the composite current collector of Comparative Example 1.

[0068] Comparative Example 2

[0069] Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that the magnetic field strength is adjusted to 450 GS, and the other conditions are consistent with Example 3, so as to obtain the composite current collector of Comparative Example 2.

[0070] The performance of the composite current collectors prepared in Examples 4 to 8 and Comparative Examples 1 to 2 was tested and compared with Example 3. The results are shown in Table 2.

[0071] Table 2

[0072]

[0073] According to Table 2, when the thickness of the conductive adhesive layer is reduced, the tensile strength TD of the obtained current collector increases, but the tensile strength MD and the bonding force both decrease. This is because the bonding area is reduced, which weakens the adhesion between the copper layers. At the same time, the reduction in the thickness of the adhesive layer affects the overall uniformity and stress distribution of the material, resulting in a decrease in the tensile strength MD. The conductive adhesive effect can block the winding and adhesion between the copper layers, so that the copper layers will not fall off due to the mutual adhesion of the copper layers, and thus the density of the composite current collector can be improved after water plating. When adjusting the heating and cooling temperatures in the preparation process, as well as adjusting the winding and unwinding speed, the performance of the obtained composite current collector will be slightly affected. This is because these factors have limited effects on the conductive colloid coating, and thus will not cause too much impact on the obtained composite current collector. However, when the conductive colloid is not sprayed on the base film, the mechanical properties of the obtained composite current collector are greatly reduced. This is because the diffusion and adhesion of copper atoms between the copper layers causes the coating to fall off, making the composite material dense and transparent, and the square resistance decreases, thereby affecting the energy density, cycle life and safety of the battery.

[0074] In summary, under the preparation conditions of Example 3 of the present invention, the prepared composite current collector has a high density while taking into account its mechanical strength such as tensile properties. Its excellent adhesion can prevent the adhesion between the copper layers during winding, so that the copper layers will not fall off due to the mutual adhesion of the copper layers. The density and tensile strength of the composite current collector can be improved after water plating, and an argon tank is added at the winding place to fill the winding chamber with argon. When winding, the argon fills the gaps in the conductive glue to play a supporting role, preventing the collapse of the membrane surface and causing defects such as deformation and wrinkles.

[0075] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, as well as parameter values ​​(e.g., temperature, pressure, etc.), mounting arrangements, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure described herein that performs the function, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, improvements, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0076] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.

[0077] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A high-density composite current collector preparation device, characterized in that: include, The mounting unit (100) comprises a mounting base plate (101), a mounting shell (102) arranged on the mounting base plate (101), an unwinding device (103) arranged on the mounting shell (102), and a rewinding device (104) arranged on the mounting shell (102); The coating unit (200) comprises a spraying section (201) arranged on the mounting shell (102), an extrusion roller (202) arranged on the spraying section (201), and an argon gas tank (203) arranged under the spraying section (201).

2. The high-density composite current collector preparation device according to claim 1, characterized in that: The spraying part (201) comprises a spraying component (201a) arranged on the mounting shell (102), and a scraping component (201b) arranged on the mounting shell (102).

3. The high-density composite current collector preparation device according to claim 2, characterized in that: The spraying assembly (201a) comprises a spraying chamber (201a-1) arranged on the mounting shell (102), and a nozzle (201a-2) arranged on the spraying chamber (201a-1).

4. The high-density composite current collector preparation device according to claim 3, characterized in that: The scraping assembly (201b) comprises a scraper (201b-1) arranged on the nozzle (201a-2), and a sawtooth rack (201b-2) arranged on the scraper (201b-1); The tip angle of the sawtooth rack (201b-2) is 60°.

5. Application of a high-density composite current collector preparation device, characterized in that: A high-density composite current collector preparation device as claimed in claim 4, wherein the application method comprises: The base film is wound on the unwinding (103) at 4×10 -3 Pa, start the device, keep the vacuum of the reel (104) at 0.5-1 Pa, plate a copper layer on the base film by magnetron sputtering, and then spray a conductive adhesive layer on the surface of the base film through a spraying part (201) by dot coating; The base film after spraying the conductive adhesive layer is heated and cooled respectively and then moved to a roll (104) under an argon atmosphere to obtain a high-density composite current collector; Wherein, the base film comprises 4.5 μm PP, PET, PE or PI.

6. The use of the high-density composite current collector preparation device according to claim 5, characterized in that: The thickness of the conductive adhesive layer is 5-10 nm.

7. The use of the high-density composite current collector preparation device according to claim 6, characterized in that: The base film is heated at a temperature of 40 to 50°C.

8. The use of the high-density composite current collector preparation device according to claim 7, characterized in that: The base film is cooled to a temperature of -20 to -10°C.

9. The use of the high-density composite current collector preparation device according to claim 8, characterized in that: The linear speed of the reeling and unreeling is 3-10 m / min.

Citation Information

Cited By

  • Composite current collector base film production device and production method thereof

    CN120421181A